Ferritin – from iron, through inflammation and autoimmunity, to COVID-19. Issue 126 (January 2022) - Mahroum, Naim; Alghory, Amal; Kiyak, Zeynep; Alwani, Abdulkarim; Seida, Ravend; Alrais, Mahmoud; Shoenfeld, Yehuda
Abstract: While it took decades to arrive to a conclusion that ferritin is more than an indicator of iron storage level, it took a short period of time through the COVID-19 pandemic to wonder what the reason behind high levels of ferritin in patients with severe COVID-19 might be. Unsurprisingly, acute phase reactant was not a satisfactory explanation. Moreover, the behavior of ferritin in patients with severe COVID-19 and the subsequent high mortality rates in patients with high ferritin levels necessitated further investigations to understand the role of ferritin in the diseases. Ferritin was initially described to accompany various acute infections, both viral and bacterial, indicating an acute response to inflammation. However, with the introduction of the hyperferritinemic syndrome connecting four severe pathological conditions such as adult-onset Still's disease, macrophage activation syndrome, catastrophic antiphospholipid syndrome, and septic shock added another aspect of ferritin where it could have a pathogenetic role rather than an extremely elevated protein only. In fact, suggesting that COVID-19 is a new member in the spectrum of hyperferritinemic syndrome besides the four mentioned conditions could hopefully direct further search on the pathogenetic role of ferritin. Doubtlessly, improving our understanding of those aspects of ferritin would enormously contribute to better coping with severe diseases in terms of treatment and prevention of complications. The origin, history, importance, and the advances of searching the role of ferritin in various pathological and clinical processes are presented hereby in our article. In addition, the implications of ferritin in COVID-19 are addressed. Highlights: Ferritin is a critical protein in iron homeostasis. Acute phase reactant has been used for long time to explain high levels of ferritin in acute inflammatory as well as acute infections. Hyperferritinemia was later introduced to include severe autoimmune and inflammatory conditions which share in common extremely elevated ferritin levels. COVID-19 was suggested to be a new member of the hyperferritinemic syndrome. Ferritin has various pathogenetic implications which are yet to be completely defined.